Memory Devices: An Electric‐Field‐Controlled High‐Speed Coexisting Multibit Memory and Boolean Logic Operations in Manganite Nanowire via Local Gating (Adv. Electron. Mater. 6/2019). (6th June 2019) - Shi, Qian; Jiang, Fengxian; Yu, Yang; Lin, Hanxuan; Kou, Yunfang; Miao, Tian; Liu, Hao; Yang, Wenting; Wang, Wenbin; Cai, Peng; Xu, Xiaohong; Guo, Hangwen; et al.
Abstract : In article number1900020, a novel approach to the realization of coexisting multi‐bit memory and Boolean logic operations in a single device unit is demonstrated by Q. Shi et al. This is achieved through the use of manganite nanowires, which interact with electric fields in such a way as to allow control of eight‐level resistive states with high accuracy. Their architecture requires a current density of just 4 × 10 1 A cm −2 to operate and exhibits a switching time of less than 8 ns.